Examining Student Perception of Readiness for Online Learning: Importance and Confidence - Martin, Florence; Stamper, Brandy; Flowers, Claudia (Online Learning, 2020)
The last two decades have seen a steady increase in the number of online courses in higher education. This survey-based study examines student readiness for online learning in 2018, through the dimensions of importance and confidence as measures of readiness. An instrument with four subscales of competencies (online student attributes, time management, communication, and technical) that measures student readiness for online learning (SROL) was developed. Reliability of student responses to an online readiness instrument and factors related to student perception are examined. Descriptive statistics and item level means for the competencies are provided. Two repeated measures ANOVAs with one-within subject factor (four subscales for importance and competency) were conducted. Online student attributes, time management, and technical competencies were rated high for importance compared to communication competencies. Students were confident in online student attributes and technical competencies compared to time management and communication. Data was also analyzed based on demographic differences. MANOVA showed significant differences based on the race (white and non-white) of the students and course format (asynchronous, synchronous, and blended) on their perceptions of online learning competencies.